Projected disease transmission, health system requirements, and macro-economic impacts of the Coronavirus Disease 2019 (COVID-19) in the Philippines - Michael Ralph M. Abrigo; Jhanna Uy; Nel Jason Haw; Valerie Gilbert T. Ulep; Kris Francisco-Abrigo (Philippine Institute for Development Studies (PIDS), 2020)
The novel Coronavirus Disease 2019 (COVID-19) is a global pandemic that has infected at least 1.2 million people and caused more than 67,000 deaths worldwide. The Philippines has recorded 3,764 confirmed cases and 177 deaths as of April 7, 2020 and has implemented an enhanced Luzon-wide enhanced community quarantine (ECQ) from March 17 to April 30 in attempts to limit population movement and curb the spread of the epidemic. Based on our disease transmission model, we project that aggressive efforts in the post-ECQ period to isolate at least 70% of infectious cases through better contact tracing, social distancing, individual or household isolation, and reduced delays in time to seek care for symptomatic cases are necessary to suppress the outbreak. Otherwise, lifting the ECQ but maintaining current conditions of delayed time to seek care for symptomatic cases merely delays the progression of the outbreak but still results in around 8% of the population infected. For all scenarios that do not successfully isolate at least 70% of infectious individuals, demands for health care resources generated by COVID-19 at the peak of the outbreak far exceed available supply in the health sector. For example, assuming no further improvements in the ability to isolate symptomatic cases post-ECQ, the country's health system would require a 1.51 million beds, 456 thousand ICU beds, 246 thousand ventilators, 727 thousand doctors, a million nurses, 91 thousand medical specialists, and 36 million PPE sets on the peak day of the outbreak in August 2020. [...]
Keywords: 330; COVID-19; disease transmission; health system resource requirements; macroeconomic impact; Philippines